Efektivitas Pelayanan Angkutan Kota Dalam Provinsi (AKDP) Terminal Marisa di Era New Normal - Rudi Rudi; Urfan Urfan (Borneo Engineering : Jurnal Teknik Sipil, 2022)
Public transportation is said to have good performance if the transportation is able to provide effective and efficient services, and is able to meet the demands of passengers as a means of transportation for the implementation of community activities. The research objectives are: 1) To determine the effectiveness of Marisa Terminal's performance in the new normal era, and 2) To determine the level of user satisfaction at Marisa Terminal in the new normal era. The research method used is the analysis of the operational performance assessment of public transport and the Likert Scale. From the results of the analysis, it was found that Marisa Terminal's performance has not been effective. This is due to the implementation of the new normal era. This affects the frequency, load factor, headway, and waiting time. The level of user satisfaction is very strong or very high. The criteria for user satisfaction level consist of physical quality, supporting physical quality, institutional quality, technical quality and interactive quality.